Characteristics of exacerbators in the US Bronchiectasis and NTM Research Registry: a cross-sectional study - Nicole C. Lapinel; Radmila Choate; Timothy R. Aksamit; Joseph Feliciano; Kevin L. Winthrop; Andreas Schmid; Sebastian Fucile; Mark L. Metersky (ERJ Open Research)
Background Exacerbations of noncystic fibrosis bronchiectasis (bronchiectasis) are associated with reduced health-related quality of life and increased mortality, likelihood of hospitalisation and lung function decline. This study investigated patient clinical characteristics associated with exacerbation frequency. Methods A cross-sectional cohort study of patients ≥18 years with bronchiectasis enrolled in the US Bronchiectasis and Nontuberculous Mycobacteria (NTM) Research Registry (BRR) September 2008–March 2020. Patients were stratified by exacerbation frequency in their 2 years before enrolment. Patient demographics, respiratory symptoms, healthcare resource utilisation, microbiology, modified bronchiectasis severity index (mBSI) and select comorbidities were collected at enrolment. Patient characteristics associated with exacerbation frequency were assessed using a negative binomial model. Results The study included 2950 patients (mean age 65.6 years; 79.1% female). Frequency of moderate to severe airway obstruction (forced expiratory volume in 1 s (FEV1) % predicted <50%; most recent measure) was 15.9%, 17.8%, and 24.6% in patients with 1, 2, and ≥3 exacerbations versus 8.9% in patients with 0 exacerbations; severe disease (mBSI) was 27.8%, 24.2% and 51.1% versus 13.2%; respiratory hospitalisation was 24.5%, 33.0% and 36.5% versus 4.1%; and Pseudomonas aeruginosa infection was 18.8%, 23.4% and 35.2% versus 11.9%. In multivariable model analysis, respiratory hospitalisation, cough, haemoptysis, P.  aeruginosa, younger age, lower FEV1% predicted, asthma, and gastro-oesophageal reflux disease were associated with more exacerbations. Conclusions These findings demonstrate a high disease burden, including increased respiratory symptoms, healthcare resource utilisation, and P.  aeruginosa infection in patients with bronchiectasis and multiple exacerbations.